Achieving inter- and transdisciplinarity in Ecohealth: insights from a rodent-borne disease project in a polycrisis era - Arpin, Isabelle; Massart, Clémence; Bourret, Vincent; Castel, Guillaume; Colombo, Valeria Carolina; Eccard, Jana; Firozpoor, Jasmin; Grzybek, Maciej; Henttonen, Heikki A.; Leirs, Herwig; McManus, Andrew; Roche, Ben; et al. (Frontiers in Veterinary Science, 2024)
IntroductionInter- and transdisciplinary research (ITDR) is increasingly promoted to address “wicked problems”, particularly in health sectors adopting approaches like Ecohealth. Our Ecohealth-inspired project on rodent-borne diseases, initiated just before the COVID-19 pandemic, provided an opportunity to evaluate ITDR implementation.MethodsWe employed a recently developed semi-quantitative evaluation method to measure our project’s success in achieving ITDR and analyzed factors influencing this achievement.ResultsThe project showed strengths in system description, team task allocation, and data sharing, but had lower scores in engaging societal actors throughout the project cycle.DiscussionWe identified the underexplored influence of problem wickedness as a critical determinant of ITDR success. Addressing rodent-borne diseases, a less wicked problem, limited engagement potential but enabled constructive dialog with local actors. These insights are vital for addressing variably wicked problems in a polycrisis era. We propose recommendations to strengthen researchers’ capacities, particularly in Ecohealth.